Teaching by principles: an approach for teaching english as a second language and how it develops communicate competence in the classroom - López Jaramillo, María Gabriela (2010)
1. Introduction 2. The communicative competence and its role in the second language acquisition 3. The twelve principles to teach english 4. Conclusions and recommendations